2001
DOI: 10.1046/j.1523-1755.2001.060002748.x
|View full text |Cite
|
Sign up to set email alerts
|

Level of hydration and renal function in healthy humans

Abstract: In fasting adults, high hydration lowered GFR and increased natriuresis. After a meat meal, GFR increased only in the high hydration regimen and natriuresis only in the low hydration regimen. Hydration affects GFR and natriuresis under fasting conditions and after a meat meal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 12 publications
10
64
1
1
Order By: Relevance
“…In two small studies of acute water loading in healthy adults, a transient increase in albumin excretion was observed in one (27), and the other showed that the effect of fluid loading on GFR was dependent on whether participants had consumed a high-protein meal or were in a fasting state (28). Anastasio et al underlined the acute nature of these experiments, which cannot be generalized to the effects of chronic high hydration (28). We previously noted an association between polyuria and 24-hour urine protein, but a subsequent investigation revealed that laboratory measurement error was the most likely explanation for these results (13,29).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In two small studies of acute water loading in healthy adults, a transient increase in albumin excretion was observed in one (27), and the other showed that the effect of fluid loading on GFR was dependent on whether participants had consumed a high-protein meal or were in a fasting state (28). Anastasio et al underlined the acute nature of these experiments, which cannot be generalized to the effects of chronic high hydration (28). We previously noted an association between polyuria and 24-hour urine protein, but a subsequent investigation revealed that laboratory measurement error was the most likely explanation for these results (13,29).…”
Section: Discussionmentioning
confidence: 98%
“…Kidneys may function more efficiently in the presence of an abundant supply of water (33). Higher fluid intake increases the clearance of sodium, urea, and osmoles (4,28,34), and high fluid intake is the most effective therapeutic measure to prevent kidney stones (6,7,35). If the kidneys are made to economize on water and produce more concentrated urine to maintain plasma osmolality, they may incur greater metabolic demand, as demonstrated in studies of rats (23,32,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the glomerular filtration rate induced by a protein meal is lower in subjects with high hydration levels than those with low hydration levels (Hadj-Aissa et al, 1992) (Figure 5c). Recently, a positive correlation has been observed between the glomerular filtration rate and urine osmolality with normal fluid intake, but not in the context of water diuresis (Anastasio et al, 2001) (Figure 5d). The normal human glomerular filtration rate is approximately 150 l/day, and 95-99.5% of the water and 99% of the sodium are reabsorbed.…”
Section: Renal Consequences Of a High Level Of Vasopressin In A Healtmentioning
confidence: 92%
“…In their very cautious analysis of these findings, the authors (21) point out: 1) that the correlations are not necessarily causal (although they may involve the effect of hydration on hemorheological variables such as blood viscosity); 2) that the findings might be unique to Seventh Day Adventists living in California, especially since they drink considerably more water and less caffeinated and alcoholic drinks than do other groups; 3) that the trends in the risks are significant only in men, whereas in women the risk of fatal coronary heart disease was as low as or lower in those drinking three or four glasses of water a day (711 to 948 ml) as in those who drank five or more glasses; and 4) that other 2 If, instead of the assumed 1,000 ml for water in solid food ( (29); some experts now quote a value of 500-750 ml for water derived from solid food (49)], then the calculated "water as fluid" of 1,675 ml comes astonishingly close to the 1,696 figure reported by Ershow and Cantor (Table 2). Total fluid intake 1,440 ml studies, likely ones with experimental design, will be needed to confirm the findings.…”
Section: Prevention Of Cancer Heart Disease and Other Conditionsmentioning
confidence: 99%